(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The study aimed at evaluating the impact of the factors influencing theformulation of an effective export marketing strategy in Indian Auto ComponentIndustries. There has been a significant increase in the quantity and qualityof international and export marketing research with respect to effectivesolutions towards export performance (Amit Banerji, Maulana Azad, 2012)However, an investigation on the impact of marketing strategy and exportperformance in a single industry is lacking. In addition, the influence ofenvironmental factors to moderate the relationship between export marketingstrategy and export performance has received little agreement. This researchaims to investigate the relationship between export marketing strategy andexport performance in auto component industry in India, as well as the influenceof moderating role of environmental factors on the relationship between exportmarketing strategy and export performance. Personal interview, literaturereview methods were used to measure export marketing strategy. The objective ofthis study is to check the relationship between export marketing strategy andexport performance. Uniquely, the moderating effect of certification appearedto moderate a few relationships between product and promotion adaptation,distribution strategy, design strategy and target market specification onexport performance. Managerial implications and suggestions for future researchwere also discussed.